CLOUD SERVER DALAM PEMBUATAN APLIKASI FOTOBLOG REALTIME BERBASIS ANDROID - Fithry Tahel (Majalah Ilmiah METHODA, 2019)
Today in the development of technology, the process of sharing photos gradually begins to develop. Where individuals who want to share photos need media to be able to share photos that are considered interesting. At present many social media can be used to share interesting photos but as students generally do not know the processes that occur in building a social media application sharing photos. Like how to build an application using a database system that is online so that it can be accessed by many people using an internet connection. To build an application that has a database so that it can be used online, a cloud server is needed, a technology service that combines computers and internet-based networks. So this technology utilizes internet media as a central server for data management. At this time Google has provided a cloud server service called Firebase.